The Relationship between Knowledge and Attitudes with the Behavior of Health Workers in Medical Waste Management in Indonesia: A Systematic Review and Islamic Perspectives - Lutvia dini Faghfirlia; Kholis Ernawati; Andri Gunawan; Rita Komalasari (Junior Medical Journal, 2022)
During the Covid-19 pandemic, there was an increase in medical waste, especially in healthcare facilities. Medical waste, if not managed properly, will potentially pollute the environment. The behavior of health workers in managing medical waste is influenced by knowledge and attitudes. The study aimed to analyze the relationship between knowledge and attitudes with the behavior of health workers in managing medical waste in Indonesia using a systematic review approach and according to an Islamic perspective. This study uses the method of literature review and systematic review. The selection of articles used the PRISMA (Preferred Reporting Items for Systematic Review and Meta-Analysis) method on the Google Scholar journal website. Search for articles with the keyword "Medical and Behavioral and Bivariate Waste." Articles were selected based on the 2020-2022 year of publication and a cross-sectional research design. The results of filtering articles using the PRISMA method obtained ten articles. The behavior of health workers in managing medical waste from the ten articles includes disposal of solid medical waste, management of medical waste, segregation of medical waste, disposal of medical and non-medical waste, management of solid medical waste, and sorting of solid medical waste. Nine articles show that there is a significant relationship between the knowledge and behavior of health workers. Eight articles show a significant relationship between the attitudes and behavior of health workers. The review of the Islamic religion concluded that health workers must have a trustworthy nature, work ethic, responsibility, and accountability. Health workers are also required to maintain personal hygiene and the environment.